THE INFLUENCE OF SHARED LEADERSHIP ON THE PERFORMANCE OF THE DKI JAKARTA PROVINCE TOURISM AND CREATIVE ECONOMY OFFICE WITH ORGANIZATIONAL COMMITMENT AS A MEDIATOR - Abdullah, Putri Allana (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to analyze the effect of shared leadership on the performance of the DKI Jakarta Provincial Tourism and Creative Economy Office with organizational commitment as a mediating variable. The method used is a quantitative approach with data processing using SEM LISREL 9.30 and SMART PLS 4.0. The research sample consisted of 105 respondents who were employees of the DKI Jakarta Tourism and Creative Economy Office. The results of the study indicate that shared leadership has a positive and significant effect on organizational performance. In addition, organizational commitment is proven to act as a mediating variable in the relationship between shared leadership and organizational performance. This indicates that the higher the level of employee commitment, the more optimal the impact of shared leadership on improving organizational performance. The conclusion of this study emphasizes the importance of cross-sector collaboration and the involvement of various stakeholders in managing the tourism sector more effectively. The recommendations of this study include the application of a SMART goals-based leadership approach to improve work effectiveness and strengthen coordination between the government and stakeholders in the tourism sector in Jakarta.